Avaliação da velocidade de onda de pulso e da pressão sistólica central em crianças e adolescentes com doença renal crônica - Brecheret, Ana Paula [UNIFESP] (2018)
Cardiovascular disease remains the most common cause of mortality in chronic kidney disease (CKD). Arterial stiffeness measured by pulse wave velocity (PWV) and central aortic blood pressure (CBP) predicts cardiovascular events and mortality in adults. Defining arterial stiffness may help to determine the cardiovascular risk in children. Objectives: Investigate pulse wave velocity among children and adolescents with CKD. Methods: In this cross-sectional study 57 patients (61.4% male), age 6.2-17.5 years, 44 with non-dialysis CKD and 13 on chronic dialysis were included in the analysis. The PWV and the CBP was measured with an oscillometric device with inbuilt ARCSolver-algorithm (estimated by using the brachial waveform) and compared with previously established percentiles for PWV and CBP. Results: The prevalence of elevated PWV was 21.1% (95%Cl: 11.4-33.9). According to Generalized Linear Model with binomial distribution and log link function there was a higher risk of elevated PWV in patients having chronic dialysis treatment when compared with non-dialysis CKD patients (adjPR=4.31, 95%CI: 1.26-14.83, p=0.020). Hypertensive patients (stage 2) have a higher risk of elevated PWV when compared with normotensives (adjPR=3.11, 95%CI: 1.17-8.24, p=0.022) as the patients younger than 12 years compared with the older patients (adjPR=3.41, 95%CI:1.25-9.29, p=0.017). Hypertensive patients (stage 1 and 2) have higher risk of elevated CBP when compared with normotensives (adjPR=3.29, 95%Cl:1.36-7.94) and patients having chronic dialysis treatment when compared with non-dialysis CKD patients (adjPR=2.08, 95%Cl:1.07-4.02). Conclusions: The findings suggest that younger ages, dialysis and hypertension in children and adolescents are independently associated with an increase in PWV and hypertension and dialysis are independently associated with an increase in CBP. Further research is needed to clarify these relations with cardiovascular complications in children and adolescents with CKD.